Incidence and Glycemic Status of Infants of Diabetic Mothers among 189 Hospitalized Low Birth Weight Babies (Delta Medical College Journal, 2017)
Background: The prevalence of gestational diabetes mellitus (GDM) is 9.7% in Bangladesh. Infants of diabetic mothers (IDM) have a significant chance to develop various complications including glucose instability.Objective: To find out the incidence of IDM among low birth weight (LBW) babies and their relation with blood glucose level during 1st 48 hours of life.Materials and method: This cross sectional study was conducted from July 2012 to June 2013 on 189 LBW babies with birth weight